Development of transfersomal emulgel to enhance the permeation of berberine chloride for transdermal delivery - Fitria Mayangsari, Silvia Surini, Raditya Iswandana (Journal of Applied Pharmaceutical Science, 2022)
The low penetration of berberine chloride (BBR) through the skin is due to its hydrophilic characteristic. Therefore, this study aims to enhance the penetration of BBR using transfersomal emulgel for transdermal delivery. Four formulations used were prepared by varying the ratio of the main ingredient concentrations and the transfersomes were also prepared by a solvent evaporation method. Subsequently, the BBR transfersomes were formulated into emulgel and in vitro penetration was carriexd out using Franz diffusion cells for 12 hours. The results showed that the best transfersome formula was F2 transfersomes, which had a deformable spherical shape, particle size (ZAverage) of 153.9 ± 2.07 nm, polydispersity index of 0.103 ± 0.033, zeta potential of −32.47 ± 0.551 mV, and entrapment efficiency of 93.97 ± 0.31%. Furthermore, the BBR transfersomal emulgel showed yellow, good homogeneity, and range from pH 7.2 to 7.4. All the formulae had drug content that ranged from 98.34% to 105.87% and the BBR penetration was much enhanced by transfersomal emulgel F2 compared to the nontransfersomal emulgel by 3.8-fold. This study showed that the transfersomal emulgel formulation provides higher levels of BBR permeation through the skin.
Keywords: Berberine chloride, transfersomes, emulgel, transdermal, in vitro penetration